The effects of human land use on the winter habitat of the recovering Carcross woodland caribou herd in suburban Yukon Territory, Canada - Florkiewicz, Rob; Maraj, Ramona; Hegel, Troy; Waterreus, Marcus (Rangifer, 2007)
Carcross woodland caribou (Rangifer tarandus caribou) numbers are increasing as a result of an intensive management and recovery program initiated in 1993. In the last 13 years, three overlapping First Nation land claim agreements were settled resulting in a complicated array of private and public land management authorities on this winter range, situated in the Whitehorse periphery. Twelve years of VHF radio-collar data (1994-2005) and 5 years of GPS radio-collar data (2000-2005) for female caribou were assessed to determine winter concentration areas and important winter habitats. We contrasted locations from 11 GPS radio-collared caribou with land cover classes, derived from classified Landsat 7 imagery, to evaluate the distribution and abundance of preferred habitats within this winter range. We found significant use of Open Needle Leaf lichen vegetation classes and avoidance of the relatively more abundant Closed Needle Leaf class. Our resource selection function model validated the preference for Open Needle Leaf Lichen and determined that caribou were spaced significantly further from an estimate of the human Zone of Influence (ZOI) than was expected from random locations. While our assessment determined that 64% of the winter range was located outside of either private lands or land influenced by human activity, key winter vegetation classes were under-represented within this area. If caribou are to successfully recover on this landscape and persist through time it is essential to manage, through meaningful participation among land management authorities, the remaining caribou habitat for environmental rather than human consumptive values.